2014
DOI: 10.1155/2014/120739
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Melanogenic Enzyme Tyrosinase from Button Mushroom

Abstract: Melanogenesis is a biosynthetic pathway for the formation of the pigment melanin in human skin. A key enzyme, tyrosinase, catalyzes the first and only rate-limiting steps in melanogenesis. Since the discovery of its melanogenic properties, tyrosinase has been in prime focus and microbial sources of the enzyme are sought. Agaricus bisporus widely known as the common edible mushroom, it's taking place in high amounts of proteins, enzyme, carbohydrates, fibers, and low fat contents are frequently cited in the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…Other workers have used ultrafiltration [66,74], acetone precipitation [75], and ethanol precipitation [76]. The next step usually involves the use of dialysis to remove ammonium sulfate traces and other impurities present in the culture medium [77,78]. Further purification is done by chromatographic technique such as gel filtration chromatography, ions exchange chromatography, adsorption chromatography, hydrophobic interaction chromatography or HPLC [68,71,79].…”
Section: Purification Of β-Glucosidasementioning
confidence: 99%
“…Other workers have used ultrafiltration [66,74], acetone precipitation [75], and ethanol precipitation [76]. The next step usually involves the use of dialysis to remove ammonium sulfate traces and other impurities present in the culture medium [77,78]. Further purification is done by chromatographic technique such as gel filtration chromatography, ions exchange chromatography, adsorption chromatography, hydrophobic interaction chromatography or HPLC [68,71,79].…”
Section: Purification Of β-Glucosidasementioning
confidence: 99%
“…It has been found that A. bisporus naturally contains large quantities of this compound. Tyrosinase acts as a catalyst in the hydroxylation of monophenol and the oxi-dation of diphenol in the presence of atmospheric oxygen [Kampmann et al, 2015;Labus et al, 2011;Zaidi et al, 2014]. It has also been shown that tyrosinase isolated from A. bisporus may catalyze bisphenol reactions, which could make this species a useful bioremediation agent [Kampmann et al, 2015].…”
Section: Tyrosinase From Fruiting Bodies Of Agaricus Bisporus and Itsmentioning
confidence: 99%
“…This enzyme was described for the fi rst time in mammals [Bloch, 1927]. Its connection with the development of melanoma has been described, as well as its link to skin pigmentation problems (such as vitiligo or albinism) [Zaidi et al, 2014]. Tyrosinase can be extracted from various sources, i.e.…”
Section: Tyrosinase From Fruiting Bodies Of Agaricus Bisporus and Itsmentioning
confidence: 99%
“…Tyrosinase extracted from white mushroom shows a high degree of similarity to the one observed in human body. Thus, this species is a valuable and concurrently inexpensive source of tyrosinase [5,12,13]. The studies conducted on the enzyme isolated from A. bisporus showed that it exhibits a protective effect on the human lymphoma cell lines, protecting them from the negative effects of damaging agents such as dihydrogen peroxide [14].…”
Section: Introductionmentioning
confidence: 99%